THE INFLUENCE OF THE DECISION OF THE INVESTIGATING JUDGE REGARDING THE GRANTING OF PERMISSION FOR THE CONDUCT OF SECRET INVESTIGATIVE (SEARCH) ACTIONS ON THE CONSTITUTIONAL RIGHTS OF A PERSON - Soroka, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the article defines the need to study the decisions of the investigating judge inseparably with the results of secret investigative (search) actions. The author conclude that the existing practice pays insufficient attention to the violation of a person’s constitutional rights, which may be allowed at the stage of consideration of a petition and the issuance of a decision on granting permission to conduct secret investigative (search) actions. Research methods: general dialectical method of scientific knowledge, comparative legal, statistical, method of scientific knowledge and hermeneutic method of interpreting legal norms. Results: generalization of the impact on a person’s constitutional rights of the illegal decisions of the investigating judge on granting permission to carry out secret investigative (search) actions. According to the authors, the mere opening to the defense of access to the materials of the NSRD and the decision, which became the legal basis for their conduct, is insufficient to maintain the balance of the interests of society and the person in respect of whom the NSRD is conducted. It is necessary to establish a mechanism for appellate appeal of decisions on granting permission to conduct NSRD with observance of all stages of the judicial process, such as keeping a log of the court session, the possibility of submitting objections and conducting debates. Discussion: the degree of influence on the constitutional rights of a person, in particular the right to the right to non-interference in personal life and the secrecy of correspondence, has been clarified. Until now, the procedural action remains rather incompletely researched - consideration of a request for permission to conduct NSRD from the point of view of compliance with the requirements of the criminal procedural law, not only in the form of a decision to grant permission for NSRD, but also the procedure of such consideration as a component of the legality of such decisions of the investigating judge.